Newton’s Method for Distance Optimization in Firefly Algorithm in Determining Optimum Nutrition for Laying Hens - M.Shochibul Burhan; Fitri Utaminingrum (INKOM Journal, 2017)
An accurate calculation of feed nutrition and more affordable price is an extremely complex. Firefly algorithm is an algorithm designed for optimization calculation whose output is highly dependent on light intensity (β), which is influenced by distance (r). Therefore, in order to produce maximum output values, an optimization of firefly distance should be done. The most appropriate method is Newton’s Method as it has the capability of solving roots of equations accurately. From the testing of distance optimization in firefly algorithm, a fairly good increase in the fitness value was obtained.Keywords: Newton Method, Firefly Algorithm